Peranan Organisasi Karang Taruna dalam Mewujudkan Tanggung Jawab Sosial Generasi Muda sebagai Gerakan Warga Negara - Simanjuntak, Tika Paskayati M; Suyato, Suyato (Jurnal Ilmiah Global Education, 2025)
This study investigates the role of the Karang Taruna organization in fostering youth social responsibility as an integral part of civic engagement in Siopat Suhu Subdistrict, Pematangsiantar City. As a community-based youth organization, Karang Taruna occupies a strategic position in character formation and in promoting the active involvement of young people in societal life. Employing a descriptive qualitative approach, data were collected through observation, in-depth interviews with organizational leaders, members, and community figures, as well as through documentary analysis. The findings reveal that Karang Taruna in Siopat Suhu has implemented a range of social programs, including communal service activities, vocational training, and educational outreach, all of which enhance awareness of the vital role of youth in social development. These initiatives contribute significantly to strengthening social responsibility, solidarity, and civic consciousness among the younger generation. Accordingly, Karang Taruna serves as a pivotal agent of social development and a catalyst for youth participation in both community and national life.